IMPLEMENTASI KONSEP BEEF (BALANCE, EYE, ELBOW, FOLLOW THROUGH) PADA PEMBELAJARAN SHOOTING BOLA BASKET - Hajaang, Yohanes; Simanjuntak, Victor G; Gustian, Uray (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThe problem in this research is the lack of students 'understanding of the basics in basketball shooting, there are still teachers (instructors) who use the same learning method and the need to learn with BEEF concepts to improve students' shooting abilities in basketball shooting. The study design used a research method with the Nonequivalent control group design, with the participation of 70 people. Sampling with non probability sampling techniques in the form of saturated sampling. Data analysis using SPSS 22. The results obtained from the lowest initial test score (pretest) 27 and the highest score 81 with an average score of 49.88, while the final test score (posttest) obtained the lowest value of 45 and the acquisition value of 100 with an average value average of 78.54, it can be seen an increase with the difference in the average value of 28.66 with 57.46% presentation. Based on the results of the analysis it can be concluded that the research hypothesis is accepted, the learning model with the BEEF concept is effective for improving basketball learning outcomes.Keywords: Beef Concept, Learning Model, Shooting, Basketball